Improving Year 5 students' learning outcomes in problem-solving through mathematical literacy. (February 2020) - Monawati; Fauzi; Husin, M; Maisarah
Abstract: Solving mathematics word problems remains as difficult tasks for elementary students. One way to overcome this problem is by applying mathematical literacy. This study aimed to describe teachers' ability in managing the learning process and determine the learning outcomes of Year 5 students. This study employed a qualitative approach, specifically Classroom Action Research. The study design was carried out in three cycles. The data collection related to teachers' ability in learning management was conducted by observation, was analysed using descriptive statistics, with the category of "poor, fair, average, good, and excellent". On the other hand, students' learning outcomes were measured by a mathematics test, were analysed by using percentages and referred to the school's minimum criteria of mastery learning. The results showed the increase in teachers' learning management ability, the average of cycle I, II and III was 4.3 (good), 4.6, and 4.8 (excellent) respectively. Besides, the students' learning outcome was also improved, the average of cycle I, II and III were 62.36 (23.5% of classical mastery learning), 66.18 (58.8% of classical mastery learning), and 85 (70.6% of classical mastery learning) respectively. The results showed that mathematical literacy could improve Year 5 students' learning outcomes in problem-solving.